2004
DOI: 10.1016/j.ijindorg.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Number of sellers, average prices, and price dispersion

Abstract: Abstract:A variety of models provide differing predictions regarding the effect of an increase in the number of competitors in a market (seller density) on prices and price dispersion. We review different approaches to generating equilibrium price dispersion and then empirically estimate the relationship between seller density, average product price, and price dispersion in the retail gasoline industry using four unique gasoline price data sets. Controlling for station-level characteristics, we find that an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
185
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(221 citation statements)
references
References 34 publications
16
185
0
8
Order By: Relevance
“…Walsh and Whelan (1999), among others, have adopted the notion of heterogeneous demand elasticity as a key source of price dispersion. Barron et al (2004) show that an increase in the own price elasticity of demand will result in a decrease in the average markups. This will lead to a reduction in price dispersion, as the increase in own price elasticity lowers prices of all sellers toward their respective marginal costs.…”
Section: Hypothesis 2 (H2) Products With Longer Order Cycle Times Armentioning
confidence: 97%
“…Walsh and Whelan (1999), among others, have adopted the notion of heterogeneous demand elasticity as a key source of price dispersion. Barron et al (2004) show that an increase in the own price elasticity of demand will result in a decrease in the average markups. This will lead to a reduction in price dispersion, as the increase in own price elasticity lowers prices of all sellers toward their respective marginal costs.…”
Section: Hypothesis 2 (H2) Products With Longer Order Cycle Times Armentioning
confidence: 97%
“…Van Meerbeeck has observed that prices vary with stations located along a highway always charge the maximum price determined by an agreement between the oil industry and the Belgian government, and prices are below the maximum price in markets with su¢ cient competition and that the number of local competitors does not have a large impact on retail gasoline prices. Barron et al (2004) have used cross-sectional gasoline price data covering 3,197 gas stations in four metropolitan areas (Phoenix, AZ, Tuscon, AZ San Diego, CA, and San Francisco, CA) for only one day in 1997 (where that one day di¤ers across metropolitan areas). They have found that an increase in station density consistently decreases both price levels and price dispersion across four geographical areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To capture the part of the local agglomeration externalities through f G g in Equation 3.14 (that have negative e¤ects on gas-station-level gasoline prices), since we have a spatial analysis of gasoline prices, we need corresponding spatial data for the size and spatial distribution of economic activity around gas station g. Accordingly, we use the standard deviation of the nighttime lights around gas station g as a proxy for f G g :…”
Section: Data For Economic Activity and Spatial Measuresmentioning
confidence: 99%
See 2 more Smart Citations